Urinary Tract Infection and Antibiotic Susceptibility at Nepalgunj Medical College and Teaching Hospital, Kohalpur - Mahaseth, Binod; Srivastava, Madhuri; Das, C. R.; Rawat, Durga (Journal of Nepalgunj Medical College, 2018)
Introduction: In developing countries, urinary tract infections (UTIs) are one of the most commonly diagnosed diseases among the patient seeking medical service and are treated with empirical antibiotics which does not provides cure and causes resistance. Objective: To find out the incidence of urinary tract infections and antibiotics sensitivity pattern among bacterial pathogens isolated in patients attending Nepalgunj Medical College and Teaching Hospital, Kohalpur. Methodology: All patients (both male and female) were included in the study with the clinical suspicion of UTI . They had their urine culture done. Incidence of UTI and spectrum of pathogens with their sensitivity were recorded. Result: A total number of 1445 patients were clinically suspected for UT. They had their urine cultura and sensitivity done Total number of patients with culture positive was 391(27.05%). The majority of isolates were from female patients comprising of 314(80.3%) patients. The most common pathogenic microorganism isolated was E.coli (73.65%). Second most common organism was Klebsiella (19.9%), it was followed by Acinetobacter (3.5%), Enterobacter (3.06%), Pseudmonas and Proteus (0.76%) each, Staphylococcus (0.05%) salmonella (0.02%). The isolated microorganisms showed maximum sensitivity to Nitrofurantin and Amikacin. The isolated microorganism demonstrated resistance to cefpodoxime and Cefotaxime. Conclusion: Urinary tract infections is a commonly encountered case in general practice Females are more commonly affected than men. The microbial profile and the antibiotic sensitivity pattern must be taken into account while planning for the management. Regular supervision of the sensitivity pattern of pathogenic microorganism is mandatory for effective treatment. JNGMC, Vol. 14 No. 2 December 2016, Page: 34-37